Preparation and characterization of high-spinnability isotropic pitch from 1-methylnaphthalene-extracted low-rank coal by co-carbonization with petroleum residue. (December 2019) - Lee, Seon Ho; Lee, Song Mi; Im, Ui-su; Kim, Sang-Do; Yoon, Seong-Ho; Lee, Byung-rok; Peck, Dong-Hyun; Shul, Yong-Gun; Jung, Doo-Hwan
Abstract: Coal extract produced by solvent extraction of low-rank coal is not suitable for spinning due to its high oxygen content. In order to effectively overcome this limitation, soft pitch was produced by co-carbonization of coal extract and petroleum residues. The decrease in oxygen content was confirmed by physical property analyses of the soft pitches blended at different mixing ratios. A bridge/hydroaromatic structure of the soft pitch was observed during the co-carbonization. The produced spinnable pitch had a high spinnability and a softening point of 230 °C. This spinnable pitch, prepared by solvent extraction of low-rank coal, showed excellent spinnability and was heat-treated at 800 °C for 5 min to produce isotropic carbon fibers having diameters of 7 μm and a tensile strength of 1189 MPa. Thus, the co-carbonization of coal extract and petroleum residue is an effective method for the production of inexpensive spinnable pitch for isotropic carbon-fiber manufacture. Graphical abstract: Image 10895